Radical Resilience: Autonomous Self-management in Post-disaster Recovery Planning and Practice. (15th March 2018) - Jon, Ihnji; Purcell, Mark
Abstract: This paper's purpose is to develop a concept of radical resilience. We do so by drawing from both agonistic and anarchist planning theory. Radical resilience exists when people mobilize their ability to manage their affairs for themselves. This ability often emerges following an agonistic conflict with a governing power. We illustrate how radical resilience looks in practice by examining three cases: New Orleans after Katrina in 2005, Indonesia after the 2004 tsunami, and Haiti after the 2010 earthquake. We conclude that the emerging field of disaster recovery planning could benefit from a close engagement with the concept of radical resilience.